Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(1^2+2^2+3^2+...+100^2\)
\(=1.\left(2-1\right)+2.\left(3-1\right)+3.\left(4-1\right)+....+100.\left(101-1\right)\)
\(=1.2-1+2.3-2+3.4-3+...+100.101-100\)
\(\left(1.2+2.3+3.4+...+100.101\right)-\left(1+2+3+...+100\right)\)
\(\Rightarrow3S=\left(1.2.3+2.3.3+3.4.3+...+100.101.3\right)-\frac{\left(1+100\right).100.3}{2}\)
\(\Rightarrow3S=\left(1.2.3+2.3.4-1.2.3+...+100.101.102-99.100.101\right)-5050.3\)
\(\Rightarrow3S=100.101.102-5050.3\)
\(\Rightarrow S=\frac{100.101.102}{3}-5050\)
\(S=1-2+2^2-2^3+.....+2^{100}\)
\(\Rightarrow2S=2-2^2+2^3-......-2^{101}\)
\(\Rightarrow3S=2S+S=\left(2-2^2+2^3-....-2^{101}\right)+1-2+2^2-2^3+....+2^{100}\)
\(\Rightarrow3S=-2^{101}+1\)
\(\Rightarrow S=\frac{1-2^{101}}{3}\)
S = 1 + 2 + 2^2 + 2^3 + 2^4 + 2^5 + ... + 2^100
2S = 2 + 2^2 + 2^3 + 2^4 + 2^5 + 2^6 + ... + 2^100 + 2^101
2S - S = ( 2 + 2^2 + 2^3 + 2^4 + 2^5 + 2^6 + ... + 2^100 + 2^101 ) - ( 1 + 2 + 2^2 +2^3 +2^4 + 2^5 + .... + 2^100 )
S = 2^101 - 1
Vậy S = 2^101 - 1
Ta có :
S = 1 + 2 + 22 + 23 + 24 + 25 + ... + 2100
2S = 2 + 22 + 23 + 24 + 25 + ... + 2101
2S - S = ( 2 + 22 + 23 + 24 + 25 + ... + 2101 ) - ( 1 - 2 - 22 - 23 - 24 - 25 - ... - 2100 )
S = 2101 - 1
S=1+2+22+23+...+2100
\(\Rightarrow\)2S= 2+22+23+...+2100+2101
\(\Rightarrow\)2S-S= (2+22+23+...+2100+2101) - (1+2+22+23+...+2100)
\(\Rightarrow\)S= (2+22+23+...+2100+2101) - (1+2+22+23+...+2100)
\(\Rightarrow\)S=2101-1
Vậy :...
giải
Ta có:
S= 1+( 2 +22+23+...+2100+2101-2101)
= 1+2*(1+21+22+...+299+2100-2100)
Khi đó: S= 1+2*(S-2100)
=> S= 1+2S-2101
<=> 2S-S=2101 -1
vậy S= 2101 -1